The Borrelia afzelii outer membrane protein BAPKO_0422 binds human factor-H and is predicted to form a membrane-spanning β-barrel. Issue 4 (18th August 2015) - Dyer, Adam; Brown, Gemma; Stejskal, Lenka; Laity, Peter R.; Bingham, Richard J.
Abstract : We present the characterization of BAPKO_0422, an outer membrane protein from Borrelia afzelii . Circular dichroism, size exclusion and small angle X-ray scattering data indicate a monomeric structure rich in β-strand. Recombinant BAPKO_0422 binds to human factor H. Abstract : The deep evolutionary history of the Spirochetes places their branch point early in the evolution of the diderms, before the divergence of the present day Proteobacteria . As a spirochete, the morphology of the Borrelia cell envelope shares characteristics of both Gram-positive and Gram-negative bacteria. A thin layer of peptidoglycan, tightly associated with the cytoplasmic membrane, is surrounded by a more labile outer membrane (OM). This OM is rich in lipoproteins but with few known integral membrane proteins. The outer membrane protein A (OmpA) domain is an eight-stranded membrane-spanning β-barrel, highly conserved among the Proteobacteria but so far unknown in the Spirochetes . In the present work, we describe the identification of four novel OmpA-like β-barrels from Borrelia afzelii, the most common cause of erythema migrans (EM) rash in Europe. Structural characterization of one these proteins (BAPKO_0422) by SAXS and CD indicate a compact globular structure rich in β-strand consistent with a monomeric β-barrel. Ab initio molecular envelopes calculated from the scattering profile are consistent with homology models and demonstrate that BAPKO_0422 adopts a peanut shape with dimensions 25×45 Å (1 Å=0.1 nm). Deviations from the standard C-terminal signature sequence are apparent; in particular the C-terminal phenylalanine residue commonly found in Proteobacterial OM proteins is replaced by isoleucine/leucine or asparagine. BAPKO_0422 is demonstrated to bind human factor H (fH) and therefore may contribute to immune evasion by inhibition of the complement response. Encoded by chromosomal genes, these proteins are highly conserved between Borrelia subspecies and may be of diagnostic or therapeutic value.